The Role of Personalized UX and UI Design in Maintaining Spotify's Dominance in the Competitive Music Streaming Industry - Fitri, Salsabila Dwi; Ananta, Yorasakhi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
The Role of Personalized UX and UI Design in Spotify's Dominance in the Digital Music Streaming Service Industry . The object of this research is Spotify as a global digital music streaming service platform . The purpose of this study is to examine the extent to which the role of personalized user experience (UX) design and effective user interface (UI) design in maintaining Spotify's dominance amidst competitive industry competition. The research method uses a literature review approach and Systematic Literature Review (SLR) with qualitative analysis. The results of the study show that Spotify's dominance is influenced by two main factors: first, UX personalization through features such as Discover Weekly , Wrapped , and Daily Mix that is able to create emotional closeness with users; second, intuitive and visually appealing UI design that improves ease of navigation and comfort of use. The conclusion of this study states that the integration of UX personalization strategies and effective UI design is an important foundation in building loyalty and retention of Spotify users sustainably.